TERMINOLOGY MANAGEMENT: CONCEPTS, PROCESSES, AND PRACTICES - Raxmonova Muxlisabonu Muminjon qizi; Muzaffarova Samiyaxon Shavkatjon qizi; G’aniyeva Tohira (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article explores the concept of terminology management, its significance in translation, scientific, and technical fields, and its implementation in modern systems. Terminology  management  involves  the  systematic  creation,  storage,  updating,  and consistent use of terms according to established standards. The paper  examines the processes of terminology management, terminological databases, Computer-Assisted Translation  (CAT)  tools,  and  corporate  terminology  systems.  It  also  highlights  the importance  of  terminology  management  in  ensuring  translation  quality,  improving workflow  efficiency,  and  supporting  intercultural  and  interdisciplinary communication.